Fear of Missing Out (FoMO) in Terms of Family Functioning in College Students - Arcivid Chorynia Ruby; Prapti Madyo Ratri; Min Yatul Rahma (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2023)
This research aims to examine the correlation between Fear of Missing Out (FoMO) in terms of family functioning. The subjects of this study consisted of 364 undergraduate students in Central Java. The research population was taken through random sampling technique. The measuring instrument in this study uses the Fear of Missing Out (FoMO) scale consisting of 20 items with reliability value of 0.384 and validity range between 0.72 to 0.94, and the family functioning scale consists of 26 items which have a reliability value 0.874 and validity items between 0.72 to 0.92. The method of data analysis in this research used statistical analysis. The quantitative data analysis technique used is Pearson's product moment correlation technique using calculations through the SPSS for windows 19.0 program. The results of this study showed that 1) There is a negative significant correlation between family functioning and Fear of Missing Out (FoMO); 2) The most influence aspects of family functioning to Fear of Missing Out (FoMO) are growth and adaptability; 3) There is 88,7% of students access the internet because of entertainment purpose; and 4) There is 50,5% of students access the internet more than 7 hours a day.